Identification of genetic diversity in the genus Musa: Proceedings of an international workshop held at Los Banos, Philippines, 5-10 Sep 1988 - Jarret, Robert L.; International Network for the Improvement of Banana and Plantain (1990)
Identification of genetic diversity occurring naturally or created by various methods is a necessity and one of INIBAP's objectives. A system has been set up comprising a transit centre (Louvain-Montpellier) to ensure control in order to distribute valuable germplasm for research. The setting up of gene banks (in vitro and/or in vivo collections) requires better identification of plant material. An international terminology (Thesaurus) and improved taxonomic methods should enable characterization in all cases of taxonomic confusion. A complete reference collection will make it possible to carry out the basic studies which are always required. In collaboration with IBPGR.